Coating of Pd and Co on Mordenite for a Catalyst of Hydrotreating of Cashew Nut Shell Liquid into Biofuel - Maya Tri Hapsari; Wega Trisunaryanti; Iip Izul Falah; Media Laila Permata (Indonesian Journal of Chemistry, 2020)
The catalytic activity of Co and Pd loaded on mordenite (MOR) was evaluated in the hydrotreatment of cashew nut shell liquid (CNSL) into biofuel. Metals were loaded into MOR as support via wet impregnation process. The Co content was varied as 2, 4, and 6 wt.% to produce Co(1)/MOR, Co(2)/MOR, Co(3)/MOR catalysts. The micro-mesoporous structure of the catalyst was confirmed by XRD, SEM, TEM, FTIR, and N2 adsorption-desorption measurement. AAS were used to analyze the amount of metal that is successfully loaded in the catalysts. Hydrotreating of the CNSL was conducted in a semi-batch reactor at 450 °C with hydrogen flow (20 mL/min) for 2 h. The liquid product was analyzed using GC-MS. The activity of Co/MOR was compared with the activity of Pd/MOR as a noble metal. The result of the hydrotreatment process showed a decrease of liquid product in the sequence of Co(3)/MOR > Co(2)/MOR > Pd/MOR > Co(1)/MOR > MOR. The Co(3)/MOR catalyst exhibited the highest conversion of liquid hydrocarbon than the others (61.8 wt.%), comprising predominantly by gasoline compounds with over 25.21 wt.% conversion.